(untitled) (Journal of Plant Disease Sciences, 2025)
Piper longum (long pepper) is an economically important spice crop affected by blight disease caused by Colletotrichum gloeosporioides, particularly during the humid monsoon months, resulting in yield losses of up to 50%. The pathogen predominantly infects the leaves and berries of the crop. In management studies, eight fungicides were evaluated at three concentrations using the poisoned food technique. Propiconazole 25% EC and tebuconazole 50% + trifloxystrobin 25% WG exhibited 100% mycelial inhibition at all tested concentrations. Additionally, four bioagents, namely Trichoderma harzianum, Trichoderma asperellum, Bacillus subtilis and Pseudomonas fluorescens, were evaluated using the dual culture technique. Trichoderma harzianum recorded the highest inhibition (65.00%), followed by Pseudomonas fluorescens (64.33%).The study highlights the effectiveness of integrating chemical fungicides with bioagents for eco-friendly management of blight disease in Piper longum.